2020
DOI: 10.3390/sym12101583
|View full text |Cite
|
Sign up to set email alerts
|

MADICS: A Methodology for Anomaly Detection in Industrial Control Systems

Abstract: Industrial Control Systems (ICSs) are widely used in critical infrastructures to support the essential services of society. Therefore, their protection against terrorist activities, natural disasters, and cyber threats is critical. Diverse cyber attack detection systems have been proposed over the years, in which each proposal has applied different steps and methods. However, there is a significant gap in the literature regarding methodologies to detect cyber attacks in ICS scenarios. The lack of such methodol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 37 publications
(64 reference statements)
0
14
0
Order By: Relevance
“…In this work, we used an open industrial dataset named Electra, 45,46 which contains protocols like the ones we found on our scenario. Specifically, Electra includes four S7Comm devices and three Modbus TCP devices.…”
Section: Deployment and Experimental Resultsmentioning
confidence: 99%
“…In this work, we used an open industrial dataset named Electra, 45,46 which contains protocols like the ones we found on our scenario. Specifically, Electra includes four S7Comm devices and three Modbus TCP devices.…”
Section: Deployment and Experimental Resultsmentioning
confidence: 99%
“…Being inherently sequential hinders parallelization within samples, which slows down training and inference processes, especially with long sequences. Therefore, work [15], [16], [17], and [18], for example, did not yield significant anomaly detection performance when employing LSTM and GRU for ICS time series data. In work [15], the author presented a data-driven predictive modeling approach for ICS systems.…”
Section: Related Workmentioning
confidence: 89%
“…The different anomaly detection approaches are evaluated on the basis of the following performance indicators: accu-racy [45], anomaly detection rate (recall) [34], false alarm rate [34], and F1-score [45] which are expressed in ( 22)- (25), respectively. The precision indicator that is needed for calculating F1-score is expressed in (26) [45].…”
Section: B Implemented Scenariosmentioning
confidence: 99%